Pemberdayaan Masyarakat di Bidang Keagamaan Melalui Majelis Ta'lim Nurul Iman Kecamatan Tanah Cogok Kabupaten Kerinci - Yaltavera, Nabila; Karni, Awis; Sihombing, Abdul Manan; Yanti, Fitra (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2023)
This research aims to determine the process of empowerment and increasing religious values. through regular recitations at the Ta`lim Nurul Iman Council, Agung Koto Iman Village, Tanah Cogok District, Kerinci Regency. The research method used is a qualitative approach with data collection through participant observation, in-depth interviews and document analysis. Research respondents were members of the Ta'lim Council and the community who were involved in routine recitation activities. The research results show that the routine recitation of the Ta`lim Nurul Iman Council is able to empower the community through 4 processes. The first process was the successful formation of the Ta`lim Nurul Iman Council group. The second process is support from the Village Head which is proof of support. The third process succeeded in determining the potential for routine recitation at the Ta`lim Nurul Iman Council. The four processes of routine recitation activities at the ta`lim assembly were successful and ran smoothly in empowering the community in the religious sector. Increasing religious values through routine recitations in the Ta`lim Nurul Iman Council of Agung Koto Iman Village, namely religious values are beliefs, worship, morals that have the potential to succeed in increasing the religious values of the people of Agung Koto Iman Village, one of which is through development progress in Nowadays, people are increasingly interested in actively studying, increasing their knowledge and understanding religious values for provisions in the afterlife, carried out every Friday and Sunday where it is held in mosques and prayer rooms.